EFEK PEMBERIAN FRAKSI YANG MENGANDUNG ALKALOID DARI BUNGA KEMBANG SEPATU (Hibiscus rosa-sinensis L.) VARIETAS MERAH TUNDUK TERHADAP AKTIVITAS MUKOLITIK SECARA IN VITRO - Ami Afiyati; Mimiek Murrukmihadi (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
Hibiscus flower (Hibiscus rosa-sinensis L.) is efficacious in cough remedies. This flower has many variations , one of which is a red flower with a crown subject. Ethanolic extract of the hibiscus flower has been studied and shown to have mucolytic activity. Fractionation will be closer in the process of finding active compounds. This study aimed to determine the effect of fractions containing alkaloids of red hibiscus flower varieties subject as mucolytics in vitro and determine the range of concentrations of the fractions equivalent to acetylcysteine effect of 0,1 %. This study included maceration, fractionation by VLC, the identification of fractions containing alkaloids, and mucolytic activity test fractions containing alkaloids. Mucolytic activity assay performed in vitro to decrease the viscosity of mucus cow. Test solutions were made with concentrations of fractions 0,4;0,6; and 0,8 %. Acetylcysteine 0,1 % was used as a positive control. Viscosity values were analyzed statistically using one -way ANOVA test , followed by the LSD test level of 95 % to determine differences between treatment groups. The results showed that the fraction containing alkaloids of hibiscus flower with a concentration of 0,4 % has not shown mucolytic activity, whereas at a concentration of 0,6 % and 0,8 % has been demonstrated in vitro mucolytic activity. Fractions containing alkaloids of hibiscus flower with a concentration of 0,6 % and 0,8 % have mucolytic activity equivalent to 0,1 % acetylcysteine in vitro.